Serum Caspase-3 And Tissue Of Cervical Intraepithelial Neoplasia (CIN) In Wistar Rats With Diethylstilbestrol Induction - Rahayu, Sri; Iting, Iting (Universitas Islam Lamongan, 2020)
Diethylstilbestrol (DES) is a synthetic estrogen hormone that is useful as hormone replacement therapy, but long-term use of DES in cervical epithelium triggers cervical intraepithelial neoplasia (CIN). CIN can develop into cervical cancer. Cervical cancer is associated with the potential for invasion and metastasis, with the gold standard is histopathological examination. Accurate diagnosis and prediction of malignancy are important issues in clinical management, including the identification of biomarkers. Caspase or Cytosolic Aspartate-Specific Cysteine Proteases (caspase) are a group of proteases that facilitate apoptosis. Caspase-3 is a key mediator of the apoptotic process that acts as an anti-cancer. Exposure to DES in rats can trigger cervical intraepithelial neoplasia. In stage CIN I, it does not need therapy because 80% of cell dysplasia can return to normal. In CIN II & III stages can develop into cancer cells (true cervical cancers precursors). CIN is called pre-cancerous cells, and it can develop into cancerous if leftÂ untreated. Â However, not all women who experience CIN will suffer cancer. The study used female Wistar rats strains for 3-5 days in age, administration a DES dose 1500 Î¼gram/KgBB for 35 days. Then examined caspase-3 contained in serum and tissue through the ELISA method. The independent t-test result showed that there was no significant difference between caspase-3 in serum and tissue with p> 0.05.